Smart Iqra’ 2 mobile learning application / Nurul Izzah Mohd Yunus and Siti Fatimah Mohd Rum - Mohd Yunus, Nurul Izzah; Mohd Rum, Siti Fatimah (College of Computing, Informatics, and Mathematics, 2024)
This project focuses on teaching the al-Quran through Iqra', a successful method that enhances children's literacy by emphasizing direct reading practice. Iqra’ consists of six volumes, covering hijaiyyah letters recognition to tajwid-compliant al-Quran recitation. Recognizing the importance of hijaiyyah letters, this project centres on Iqra' 2, introducing "baris atas" of hijaiyyah letters, connections of hijaiyyah letters, and hijaiyyah letters pronunciation. Mobile learning (m-learning) is explored for its potential to engage learners, especially preschool teachers interested in enhancing educational systems. Challenges like children's disinterest in learning al-Quran and the lack of systematic teaching aids are addressed. The project aims to design a 2-dimensional storyboard, develop instructional content for Smart Iqra’ 2, and evaluate its usability. To develop this project, the methodology that is being used is the ADDIE model. This methodology is being used in this application because it is widely recognized and adopted in instructional design. Based on testing conducted with 33 preschooler respondents, the System Usability Scale (SUS) has confirmed that Smart Iqra’ 2 is user-friendly, scoring an excellent 82.5%. This result assures an engaging and systematic mobile learning (m-learning) approach, promising optimal Quranic education experiences. In future work, the project plans to broaden the Quranic content coverage, encompassing advanced topics and levels to cater to diverse learning needs. Furthermore, an exploration into platform variation will be undertaken to enhance accessibility, ensuring the Smart Iqra' series is adaptable across various devices and operating systems for a more inclusive educational experience.